PROFIL PERMINTAAN CABAI RAWIT PADA RUMAH TANGGA PEDESAAN DI KABUPATEN JEMBER - Rahman, Rena Yunita; Zainuddin, Ahmad; Suciati, Luh Putu; Magfiroh, Illia Seldon; Setyawati, Intan Kartika (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
The price of cayenne pepper, which tends to fluctuate, will have implications for demand. In addition, consumer income, age, education, number of consumer family members, and access to financial institutions have the potential to affect consumer demand. This study aims to (1) analyze the level of demand for cayenne pepper based on consumer income levels, and (2) analyze the determinants of cayenne pepper demand. This research was conducted in Jember Regency, East Java. The sample used in this study was 120 people. The analytical method used is the calculation of average consumption and multiple linear regression analysis. The results showed that the level of income had little effect on the level of consumption of cayenne pepper in rural Jember Regency. Factors that have a significant effect on the demand for cayenne pepper in rural households in Jember Regency are the variables of consumer age, consumer education, chili price, location dummy, number of family members, and financial inclusion dummy.